Study of the selectivity of SnO2 supported membranes prepared by a sol-gel route - Santos, LRB; Larbot, A.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Kluwer Academic Publ, 1998)
In this work the sol-gel process was used to prepare SnO2 supported membranes with an average pore size of 2.5 nm. The effects of salt concentration (NaCl or CaCl2) and of the pH of the aqueous solutions used on the flux and selectivity through the SnO2 membrane were analyzed by permeation experiments and the results interpreted taking account of the zeta potential values determined from the electrophoretic mobility of the SnO2 powder aqueous dispersion. The results show that the ion flux (Na+, Ca2+ and Cl-) throughout the membrane is determined by the electrostatic repulsion among these species and the surface charge at the tin oxide-solution interface.
Keywords: SnO2 membranes; ultrafiltration; selectivity; rejection capacity